Construction of Comprehensive Dosage-Matching Core Histone Mutant Libraries for Saccharomyces cerevisiae. Issue 4 (30th November 2017) - Jiang, Shuangying; Liu, Yan; Wang, Ann; Qin, Yiran; Luo, Maoguo; Wu, Qingyu; Boeke, Jef D; Dai, Junbiao
Abstract: Saccharomyces cerevisiae contains two genes for each core histone, which are presented as pairs under the control of a divergent promoter, i.e., HHT1 -HHF1, HHT2 -HHF2, HTA1 -HTB1 and HTA2 -HTB2 . HHT1 -HHF1, and HHT2 -HHF2 encode histone H3 and H4 with identical amino acid sequences but under the control of differently regulated promoters. Previous mutagenesis studies were carried out by deleting one pair and mutating the other one. Here, we present the design and construction of three additional libraries covering HTA1 -HTB1, HTA2 -HTB2, and HHT1 -HHF1 respectively. Together with the previously described library of HHT2 -HHF2 mutants, a systematic and complete collection of mutants for each of the eight core S. cerevisiae histone genes becomes available. Each designed mutant was incorporated into the genome, generating three more corresponding libraries of yeast strains. We demonstrated that, although, under normal growth conditions, strains with single-copy integrated histone genes lacked phenotypes, in some growth conditions, growth deficiencies were observed. Specifically, we showed that addition of a second copy of the mutant histone gene could rescue the lethality in some previously known mutants that cannot survive with a single copy. This resource enables systematic studies of function of each nucleosome residue in plasmid, single-copy, and double-copy integrated formats.